1954
DOI: 10.1172/jci102977
|View full text |Cite
|
Sign up to set email alerts
|

Body Water and Sodium in Patients With Acromegaly 1

Abstract: The acromegalic state often is accompanied by an enlargement of the soft tissues of the body. The purpose of the present work was to determine whether these tissue changes are accompanied by changes in the content and distribution of water and electrolytes in the body. In this connection the administration of growth hormone was shown to induce an increase in the total body water of normal (1-4) and hypophysectomized (5) rats, and of normal dogs and cats (3). Similarly, growth hormone caused a retention of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 16 publications
(15 reference statements)
3
38
1
Order By: Relevance
“…We found that Aip +/− mice exhibit a slightly enhanced total body weight at 3 and 7 months but not at 12 months of age. The increased lean mass of Aip +/− mice could be related to body fluid retention (Ikkos et al 1954, O'Sullivan et al 1994, Kamenický et al 2014), but we did not determine total body water. Fat mass increased with age in both Aip +/− and WT mice but to a lesser extent in the mutants, possibly explaining the similar total body weights of 12-month-old mutant and WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Aip +/− mice exhibit a slightly enhanced total body weight at 3 and 7 months but not at 12 months of age. The increased lean mass of Aip +/− mice could be related to body fluid retention (Ikkos et al 1954, O'Sullivan et al 1994, Kamenický et al 2014), but we did not determine total body water. Fat mass increased with age in both Aip +/− and WT mice but to a lesser extent in the mutants, possibly explaining the similar total body weights of 12-month-old mutant and WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…GH plays an important role in the regulation of body composition, promoting a lean phenotype by increasing lipolysis in WAT and enhancing protein synthesis in muscle (Møller & Jørgensen 2009). In humans, acromegaly leads to an increase in body water and lean body mass (Ikkos et al 1954, O'Sullivan et al 1994, Kamenický et al 2014, associated with a reduction in body fat (Freda et al 2008, Katznelson 2009. Similarly, giant bovine-GH transgenic mice (bGH) exhibit a lower body fat percentage, smaller WAT deposits and lower serum leptin levels (Berryman et al 2004, Benencia et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium and fluid retaining impact of GH was demonstrated in humans almost 50 years ago by Ikkos et al [49] . Underlying mechanisms of GH-induced fluid retention are as follows.…”
Section: Resul Resul Resul Resul Results Ts Tsmentioning
confidence: 97%
“…This second hypothesis seems to us more plausible considering that in acromegaly a progressive overgrowth of connective tissue occurs throughout the body [13]. Nevertheless, the hypothesis that an increase in ocular pressure may be facilitated by excessive production of aque ous humor or by the accumulation of intra ocular fluid cannot be dismissed since ex perimentally HGH has been shown to be apt to increase total body water [18], Like wise, in acromegaly an increase in total body water and extracellular water has been ob served as well as an increase in exchange able sodium [14].…”
Section: Discussionmentioning
confidence: 99%